(3GdJCejf ef GdeSFhdjI GdeOfjI aj VhA bhGYO GdeSFhdjI aj GdJTQjY GdCQOfj (B/ s - (3ehSi Lejd EHQGgje GdfYjeGJs; (3fRjg eMeO GdUGOb GdegOjs; (3LGeYI GdOhd GdYQHjIs (3eYgO GdHMhK hGdOQGSGJ GdYQHjIs ((3GdbGgQI (B:s (3eYgO GdHMhK hGdOQGSGJ GdYQHjI (B- (3LGeYI GdOhd GdYQHjI,s, 2003)
(3JHOC gPg GdQSGdI HaUd JegjOj Yf GdeSFhdjI GdeOfjI aj GdJTQjY GdCQOfj hGdJTQjYGJ GdebGQfI (B((3GdeUQj hGdEfLdjRj(B)(3, Ke JfbSe Edi HGHjf; MjK jJfGhd GdHGH GdChd GdfXQjI GdYGeI ddJCejf ef CYHGA GdeSFhdjI, hGdHGH GdKGfj jJfGhd CKQ GdJCejf ef CYHGA GdeSFhdjI GdeOfjI Ydi JYOjd CMcGegG(B.s
(3QSGFd fSNI efaQOIs
(3CWQhMI (B((3eGLSJjQ(B)-(3LGeYI GdOhd GdYQHjI, eYgO GdHMhK hGdOQGSGJ GdYQHjI, bSe GdHMhK hGdOQGSGJ GdbGfhfjI (B2003.s
(3jTJed Ydi EQLGYGJ HjHdjhLQGajI(B: 392-408 (3UaMIs
Keywords: (3GdbGfhf GdeOfjs; (3GdfXQjI GdYGeI ddJCejfs; (3GdNWQ GdeDef efgs; (3fWGb GdJCejfs; (3CYHGA GdeSFhdjIs; (3GdeDef hGdeDef dgs; (3QSGFd LGeYjIs -- (3LGeYI GdOhd GdYQHjIs -- 2003.